Thermoluminescence response of dysprosium doped strontium tetraborate glasses subjected to electron irradiations - Lim, Tou Ying (Elsevier Ltd, 2015)
The paper presents the thermoluminescence (TL) response of strontium tetraborate glass subjected to electron irradiations at various Dy2O3 concentrations ranging from 0.00 to 1.00mol%. All glass samples exhibited single broad peak with maximum peak temperature positioned at 170-215°C. The optimum TL response was found at Dy2O3 concentration 0.75mol%. This glass showed good linearity and higher sensitivity for 7MeV compared to 6MeV electrons. Analysis of kinetic parameters showed that the glasses demonstrate second order kinetic.